Obstacles to Birth Surname Retention Upon Marriage: How Do Hostile Sexism and System Justification Predict Support for Marital Surname Change Among Women? - Chayinska, Maria; Uluğ, Özden Melis; Solak, Nevin; Kanık, Betül; Çuvaş, Burcu (Frontiers in Psychology, 2021)
Despite the ongoing shift in societal norms and gender-discriminatory practices towards more equality, many heterosexual women worldwide, including in many Western societies, choose to replace their birth surname with the family name of their spouse upon marriage. Previous research has demonstrated that the adherence to sexist ideologies (i.e., a system of discriminatory gender-based beliefs) among women is associated with their greater endorsement of practices and policies that maintain gender inequality. By integrating the ideas from the system justification theory and the ambivalent sexism theory, we proposed that the more women adhere to hostile and benevolent sexist beliefs, the more likely they would be to justify existing gender relations in society, which in turn, would positively predict their support for traditional, husband-centered marital surname change. We further argued that hostile (as compared to benevolent) sexism could act as a particularly strong direct predictor of the support for marital surname change among women. We tested these possibilities across three cross-sectional studies conducted among women in Turkey (Study 1, N = 118, self-identified feminist women; Study 2, N = 131, female students) and the U.S. (Study 3, N = 140, female students). Results of Studies 1 and 3 revealed that higher adherence to hostile (but not benevolent) sexism was associated with higher support for marital surname change indirectly through higher gender-based system justification. In Study 2, the hypothesized full mediation was not observed. Consistent with our predictions, in all three studies, hostile (but not benevolent) sexism was found to be a direct positive predictor of the support for marital surname change among women. We discuss the role of dominant ideologies surrounding marriage and inegalitarian naming conventions in different cultures as obstacles to women’s birth surname retention upon marriage.